Pseudocercospora liebenbergii PENYEBAB PENYAKIT BERCAK DAUN TANAMAN AKAR TIKUS - DONO WAHYUNO; DYAH MANOHARA (Jurnal Penelitian Tanaman Industri, 1998)
Pseudocercospora liebenbergii the cause of leaf spot disease on Rauwolfta serpentinaThe experiments wee conducted at Reseach Institute for Spice and Medicinal Crops, rom Ocober 1995 o March 19%. The objective of the experiments wee to identify the causal agent of leaf spot disease on Rauwofia serpentina and some ecobiological aspects. The expeiments were divided into two steps. The first step was observation on the disease intensity and identification of the causal agent. The second step was testing the effect of temperature and light on the mycelia growth and the germination of conidia, and the survival of conidia at diferent ranges of elative humidity. The results showed that the pathogenic of leaf spot disease is Pseudocercospora liebenbergii, newly eported pathogenic fungus in Indonesia. The fungus infected leaf only. The disease intensity ranged between 0-85%/plant with the average 22.23%. The first symptoms i.e. light spots wee observed 2-3 weeks after the inoculation. Stroma wee found on the upper and botom of the oldest spots The optimum temperatue for fungal growth ranged between 20-28°C. Continuous light was able o induce the growth of aerial mycelia but failed against the fungal rate. The germination of conidia occured at temperature between 20-32°C with an optimum of 24°C. Conidia on the surface of the oldest leaf spots were still viable ater the leaves wee incubated for 48 hours at 55% elative humidity.